2011
DOI: 10.1007/s00264-011-1231-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of the percutaneous pinning of proximal humerus fractures with a modified palm tree technique

Abstract: Purpose Many techniques are available for closed reduction and percutaneous fixation of proximal humeral fractures. The palm tree technique was described by Kapandji in 1989. In that technique three curved wires are inserted through one hole at the V-shaped insertion of the deltoid muscle. It is a good technique but it has some disadvantages. In this study we introduced some modifications for the technique, and we evaluated the clinical results of the modified technique in treatment of 18 cases. Methods Eighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Previous reports on proximal humerus fractures treated with external fixation found a 6%-19% infection rate. [15][16][17] The 39.1% infection rate in the current study is based on clinical diagnosis with only partial confirmation through positive cultures. These liberal criteria may be responsible for the high rate compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on proximal humerus fractures treated with external fixation found a 6%-19% infection rate. [15][16][17] The 39.1% infection rate in the current study is based on clinical diagnosis with only partial confirmation through positive cultures. These liberal criteria may be responsible for the high rate compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The use of percutaneous pinning may or may not involve application of an external fixator. Some surgeons cut the pins short just outside the skin, 17 other surgeons cut the pins and bury them under the skin to prevent pin tract infection, 16 while others use an external fixator device to connect the pins. 15,18 The use of an external fixator was shown to result in fewer cases of pin migration, secondary displacement, and need for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Le Bellec et al [13], reviewing 31 cases treated with the Kapandji method for 19 two-and 12 three-part proximal humerus fractures, reported 26 % of pin migration, increasing to more than 40 % in patients older than 60 years. More recently, El-Alfy [5] proposed to introduce the K-wires into independent holes to avoid the problem of migration. He reported 77 % good or excellent results and only one case of pin migration in a series of 18 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors are experienced in this technique and have reported the results, including simple and complex fractures [5,13,14,19,28]. The purpose of our study was to evaluate clinical and radiographic outcomes of complex three-or four-part proximal displaced humeral fractures treated with Kapandji pinning and additional fixation of the tuberosities.…”
Section: Introductionmentioning
confidence: 99%
“…9,17-20 Insufficient pin number or poor pin placement (ie, convergent) results in minimal fixation and fracture stability. 19,24,25 Infected pin sites require aggressive treatment consisting of pin removal, antibiotics, and deep debridement if not responding immediately. With subchondral pin penetration, the pin has no end-point and can migrate through the bone into the joint.…”
Section: Complicationsmentioning
confidence: 99%